Pengaruh Kompetensi, Budaya Organisasi dan Stres Kerja Terhadap Kinerja Karyawan PT XYZ - Elma Putri Nabila; Muhammad Asif Khan; Eri Bukhari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to measure the influence of competence, organizational culture and work stress on the performance of PT XYZ employees. This research uses quantitative research methods with a questionnaire using a sample of 121 respondents. This research uses the Partial Least Squares (PLS) data analysis method. The results of this research show that the competency variable has no significant effect on the performance of PT -values ​​0.000 < 0.05 and t-statistic value 4,296 > 1.98 and the work stress variable influences the performance of PT t-table is 2,118 > 1.98.